The Effectiveness of Close and Explicit Reading Instructions to Enhance Reading Comprehension to Highy and Lowly Motivated Students - Kusumawanti, Windhariyati Dyah; Anggani Linggar Bharati, Dwi (English Education Journal, 2018)
This study was a quasi-experimental study aimed to find out theeffectiveness of close reading and explicit reading instructions to enhance the students’ reading comprehension to students with high and low motivation. The samples of this research were the second semester students of Islamic Business and Economics Faculty at Public Islamic Institute of Purwokerto in the academic year of 2016/2017. There were nine classes that belonged to Islamic Business and Economics Faculty. For the purpose of this study, there were only two classes selected to be the samples. The first group was the first experimental group in which it was taught by close reading instruction and the other one was the second experimental group taught by explicit reading instruction. The result of this study showed that close reading instruction was not effective to enhance the students’ reading comprehension to students with high and low motivation. In addition, explicit reading instruction was also not effective to enhance the students’ reading comprehension to students with high and low motivation. Therefore, there was no interaction among teaching techniques (close and explicit reading instructions), motivation (students with high and low motivation), and reading comprehension. To sum up, close reading and explicit reading instructions did not contribute a significant difference to enhance reading comprehension to the students with high and low motivation